Translocation of IGF-1R in endoplasmic reticulum enhances SERCA2 activity to trigger Ca2+ER perturbation in hepatocellular carcinoma - Yanan Li; Keqin Li; Ting Pan; Qiaobo Xie; Yuyao Cheng; Xinfeng Wu; Rui Xu; Xiaohui Liu; Li Liu; Jiangming Gao; Wenmin Yuan; Xianjun Qu; et al. (Elsevier, 2023)
The well-known insulin-like growth factor 1 (IGF1)/IGF-1 receptor (IGF-1R) signaling pathway is overexpressed in many tumors, and is thus an attractive target for cancer treatment. However, results have often been disappointing due to crosstalk with other signals. Here, we report that IGF-1R signaling stimulates the growth of hepatocellular carcinoma (HCC) cells through the translocation of IGF-1R into the ER to enhance sarco-endoplasmic reticulum calcium ATPase 2 (SERCA2) activity. In response to ligand binding, IGF-1Rβ is translocated into the ER by β-arrestin2 (β-arr2). Mass spectrometry analysis identified SERCA2 as a target of ER IGF-1Rβ. SERCA2 activity is heavily dependent on the increase in ER IGF-1Rβ levels. ER IGF-1Rβ phosphorylates SERCA2 on Tyr990 to enhance its activity. Mutation of SERCA2-Tyr990 disrupted the interaction of ER IGF-1Rβ with SERCA2, and therefore ER IGF-1Rβ failed to promote SERCA2 activity. The enhancement of SERCA2 activity triggered Ca2+ER perturbation, leading to an increase in autophagy. Thapsigargin blocked the interaction between SERCA2 and ER IGF-1Rβ and therefore SERCA2 activity, resulting in inhibition of HCC growth. In conclusion, the translocation of IGF-1R into the ER triggers Ca2+ER perturbation by enhancing SERCA2 activity through phosphorylating Tyr990 in HCC.